Efektivitas Program Magang Guru Terhadap Retensi Guru: Systematic Literature Review (2020-2025) - Febriana, Amelia; Sugiarto, Sugiarto; Zulaikha, Siti; Mayasari, Linda Ika; Takdir, Muhammad; Syam, Aldo Redho (Proceeding of Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2025)
High rates of teacher attrition remain a global challenge that undermines the quality and continuity of education. One strategy considered effective for improving teacher retention is internship or residency programs that provide structured field experiences prior to entering the profession. This study analyzes the effectiveness of teacher internship programs on teacher retention using a Systematic Literature Review (SLR) approach based on the PRISMA 2020 method. Of the 114 articles identified through Scopus and Google Scholar, 22 met the established inclusion criteria. The analysis employed thematic synthesis to identify patterns, determining factors, and program models that contribute to teacher retention. The findings indicate that internship programs have a significant positive impact, particularly during the first five years of teaching. Their effectiveness is shaped by personal factors, structural components, and policy support. University–school partnership–based teacher residency models emerged as the most effective approach. These findings highlight the importance of designing comprehensive and sustainable internship programs to strengthen teacher retention and support the long-term viability of the teaching profession.